NGTS-19b: a high-mass transiting brown dwarf in a 17-d eccentric orbit. Issue 2 (22nd May 2021) - Acton, Jack S; Goad, Michael R; Burleigh, Matthew R; Casewell, Sarah L; Breytenbach, Hannes; Nielsen, Louise D; Smith, Gareth; Anderson, David R; Battley, Matthew P; Bayliss, Daniel; Bouchy, François; Bryant, Edward M; et al.
ABSTRACT: We present the discovery of NGTS-19b, a high-mass transiting brown dwarf discovered by the Next Generation Transit Survey. We investigate the system using follow-up photometry from the South African Astronomical Observatory, as well as sector 11 Transiting Exoplanet Survey Satellite data, in combination with radial velocity measurements from the CORALIE spectrograph to precisely characterize the system. We find that NGTS-19b is a brown dwarf companion to a K-star, with a mass of 69.5 ^+5.7_-5.4 M Jup and radius of 1.034 ^+0.055_-0.053 R Jup . The system has a reasonably long period of 17.84 d, and a high degree of eccentricity of 0.3767 ^+0.0061_-0.0061 . The mass and radius of the brown dwarf imply an age of 0.46 ^+0.26_-0.15 Gyr, however, this is inconsistent with the age determined from the host star spectral energy distribution, suggesting that the brown dwarf may be inflated. This is unusual given that its large mass and relatively low levels of irradiation would make it much harder to inflate. NGTS-19b adds to the small, but growing number of brown dwarfs transiting main-sequence stars, and is a valuable addition as we begin to populate the so-called brown dwarf desert.